Development of TRIGA Fuel Fabrication by Powder Technique - H. Suwarno (PPIKSN-BATAN, 2014)
The prospect of operation of the Indonesian TRIGA reactors may be jeopardizes in the future due to the lack of fuel and control rods. Both fuel and control rods may not longer be imported and should be developed domestically. The most specific technology to fabricate TRIGA fuel rod is the production of UZrH1.6 pellet. The steps include converting the massive U metal into powder in by hydriding-dehydriding technique and mixing the U and Zr powders. A research has been planned to conducted by the National Nuclear Energy Agency (BATAN) in Indonesia. Fixed amount of U-Zr mixed powders at the ratio of U/Zr = 10 wt% was pressed into a pellet with a diameter of 1.41 in and a thickness of 1 or 1.5 in, sintered at a temperature of 1200oC, followed by hydriding at 800oC to obtained UZrH1.6. The pellets, cladding, and other components were then fabricated into a fuel rod. A detailed discussion of the TRIGA fuel fabrication is presented in the paper. Received: 22 October 2014; Revised: 29 December 2014; Accepted: 31 December 2014